Hubungan Antara College Adjusment dan Stres Akademik Pada Mahasiswa Baru Fakultas Psikologi Universitas Negeri Makassar - Isabella Juli Tresnadi; Ahmad; Novita Maulidya Djalal (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The transition period from student to college student experiences various changes in the process, such as higher demands and workloads in college compared to high school. These demands can put pressure on new students in carrying out their academic activities. The inability of new students to cope with this pressure gives rise to academic stress. One of the factors that influences the occurrence of academic stress is the level of adjustment to college of new students. This study aims to determine the relationship between college adjustment and academic stress. The sample in this study consisted of 224 new students class of 2022, Faculty of Psychology, Makassar State University. Data collection was carried out using 2 research instruments, namely the academic stress scale and the college adjustment scale. Hypothesis testing was carried out using Karl Pearson's Product Moment method. The research results show that there is a negative relationship between college adjustment and academic stress with a correlation value of r = -0.514 and a significance value of 0.000 (p < 0.05). This means that the higher the level of college adjustment, the lower the level of academic stress experienced by new students. The R square value in this study was 0.264, which shows that the contribution of college adjustment to the academic stress of new students is 26.4%. What this research means is that new students need to have a good level of adjustment to college in order to be able to face the demands and pressures of dealing with academic stress.